MOQARE: misuse-oriented quality requirements engineering - Herrmann, Andrea; Paech, Barbara (Requirements engineering, 2008)
This work presents MOQARE (misuse-oriented quality requirements engineering), a method to explore quality requirements. The aim of MOQARE is to support intuitive and systematic identification of quality requirements. It was developed by integrating and adapting concepts from other methods (like Misuse Cases). It provides a general conceptual model of quality requirements, and a checklist-based process for deriving them in a top-down fashion. This derivation starts from business goals and vague quality requirements and delivers detailed requirements. MOQARE applies to requirements on the system to be developed requirements, but also derives requirements on the development process, including administration and maintenance. It considers normal and extreme use. The relationships among these requirements are modeled in a Misuse Tree. MOQARE has shown its merits in several case studies, one of which is presented here.